Wild Beans (Phaseolus L.) of North America - Dohle, Sarah; Berny Mier y Teran, Jorge Carlos; Egan, Ashley; Kisha, Theodore; Khoury, Colin K. (Springer, 2019)
The wild relatives of the five domesticated species of bean (Phaseolus L.) are widely distributed across the tropics and subtropics of the New World, with taxa extending from the Canadian border to Argentina, and on the Caribbean Islands, Bermuda, and the Galapagos Islands. Mesoamerica holds the largest concentration of species, particularly in the highlands of central Mexico, northward along the Sierra Madre Occidental, and south to Chiapas. The progenitors and close relatives of all five domesticates are also concentrated in this region. Plant breeding involving the use of wild relatives has almost entirely been directed toward the improvement of common bean (Phaseolus vulgaris L.), the most widely cultivated species, and successful contributions have mostly come from its progenitor (Phaseolus vulgaris L.) and a few other taxa. Wild relatives are considered to possess novel useful genetic variation that has not yet been fully explored. A number of wild Phaseolus are rare endemics that are threatened in their natural habitats and are insufficiently protected in situ. Significant ex situ collections of wild Phaseolus are maintained at the International Center for Tropical Agriculture (CIAT), the USDA-ARS National Plant Germplasm System, within the Sistema Nacional de Recursos Fitogenéticos para la Alimentación y la Agricultura (SINAREFI) Conservation Centers Network in Mexico, and at the Botanic Garden Meise, Belgium. Unfortunately, over 26% of Phaseolus taxa are not represented at all in these ex situ conservation facilities, and another 29% are represented by less than ten accessions, making over half of the species highly underrepresented in genebanks. Further efforts to enhance the protection of vulnerable species in their natural habitats, and further collecting to fill critical gaps in germplasm collections, are warranted.